Dinamika Perkembangan Musik Tongling di Dusun Wonomulyo, Kabupaten Magetan, Jawa Timur (1985- 2025) - Mutiara Dewi Fatimah; Galib Satrio Wicaksana; Sigit Purwanto (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research discusses the dynamics of the development of Tongling music as a local cultural heritage in Wonomulyo Hamlet, Magetan Regency, especially those that occurred in the 1985-2025 era. The word “Tongling” is an acronym for the words ‘kentongan’ and “suling” where the two instruments are the musical instruments that characterize the Tongling ensemble. A qualitative approach with an analytic descriptive method was used to dig deeply into the dynamic process that occurred. Data collection was carried out by interviewing selected resource persons, observation, and literature and webtography studies. Social identity theory and social dynamics theory were used as a premise to analyze the shifting functions and roles of Tongling music. The results show that Tongling music has undergone a significant development process in the three periods of leadership of the Nichiren Shoshu Buddhist Pandita characterized by instrument innovation, the involvement of the younger generation, and the direction of opening Tongling music to all levels of society who are interested without considering religious beliefs. These changes have not only expanded the reach of Tongling music but also strengthened the cultural identity of the Wonomulyo community in Magetan.